2002
DOI: 10.1111/j.1745-4522.2002.tb00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Health Promoting Constituents in Plant Derived Edible Oils

Abstract: Of all the edible oils, only that produced from olives has had its health attributes studied in detail. For maximum nutritional benefit, an edible oil should contain minimal levels of saturated fats, especially lauric and myristic acids and minimal levels of trans fatty acids. If the oils are not to be heated repeatedly and if they contain high levels of antioxidants, they should contain omega‐3 and possibly omega‐6 polyunsaturated fatty acids. The fatty acid profile should be dominated by monounsaturated fatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 139 publications
1
22
0
2
Order By: Relevance
“…Such values were one order of magnitude higher than that reported by Colquhoun, Hicks, and Reed (1996) (2 mg/g oil ). However, these data seemed to confirm the reduced polyphenol content of grape seed oil when compared to that of olive oil, for which values up to 1700 mg/g oil were reported (Beardsell, Francis, Ridley, Robards, 2002).…”
Section: Extraction Form Grape Marcmentioning
confidence: 57%
“…Such values were one order of magnitude higher than that reported by Colquhoun, Hicks, and Reed (1996) (2 mg/g oil ). However, these data seemed to confirm the reduced polyphenol content of grape seed oil when compared to that of olive oil, for which values up to 1700 mg/g oil were reported (Beardsell, Francis, Ridley, Robards, 2002).…”
Section: Extraction Form Grape Marcmentioning
confidence: 57%
“…It is suggested that in Atlantic salmon, 75 % of dietary fish oil can be replaced by vegetable oil without compromising growth and performance or significantly affecting fish health or welfare if n-3 LC-PUFA requirements are met (19,35,43) . Vegetable oils do not contain any n-3 LC-PUFA, but can contain higher concentrations of SFA (in the case of palm oil), MUFA and n-6 PUFA (44) . Salmon fed replacement vegetable oils have a reduced n-3 LC-PUFA content, which is a reflection of these diets.…”
Section: Lipid Content and Nutrition Of Aquafeedsmentioning
confidence: 99%
“…Lampi ve ark. (37), yüksek oranda γ tokoferol ve oleik asit içeren kanola ve soya ya¤lar›n›n k›zartma iflleminde polimerizasyon oluflumuna karfl› direnç gösterdi¤ini belirtmifltir. Warner ve ark.…”
Section: çEvresel Faktörler Sıcaklıkunclassified